2016
DOI: 10.13102/sociobiology.v63i2.936
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of plant extracts from Bahia, Brazil, to Atta sexdens sexdens workers (Hymenoptera: Formicidae)

Abstract: Ants of the Atta and Acromyrmex genera (Formicidae: Myrmicinae: Attini) are the true leaf cutting-ants with species of economic importance in America Neotropical and mainly controlled by toxic baits. There are few active ingredients for use in baits, being necessary studies to indicate molecules with insecticide potential. The aim of this study was to evaluate the toxicity of . The contact and ingestion toxicity of all extracts to this ant by was evaluated by topical application and addition in their diet, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…For the treatments 10, 14, 18, and 20% there was no survival in the period of 24 hours after topical application, evidencing its mortality after contact with the extract. Gomes et al (2016) observed toxic effect by contact of extracts of leaves and branches of Zanthoxylum rhoifolium, bark of Simarouba amara, branches of Aspidosperma spruceanum, and leaves of Casearia arborea on Atta sexdens sexdens. According to these same authors the extracts of plants of the Rutaceae family have toxicity to A. sexdens sexdens and also to other insects and should be further studied.…”
Section: Resultsmentioning
confidence: 89%
“…For the treatments 10, 14, 18, and 20% there was no survival in the period of 24 hours after topical application, evidencing its mortality after contact with the extract. Gomes et al (2016) observed toxic effect by contact of extracts of leaves and branches of Zanthoxylum rhoifolium, bark of Simarouba amara, branches of Aspidosperma spruceanum, and leaves of Casearia arborea on Atta sexdens sexdens. According to these same authors the extracts of plants of the Rutaceae family have toxicity to A. sexdens sexdens and also to other insects and should be further studied.…”
Section: Resultsmentioning
confidence: 89%
“…However, the chemical control may cause detrimental effects on the environment and to men; as a result, sulfluramid, the principal compound now used, is about to be prohibited (STOCKHOLM CONVENTION, 2008). Hence, research has advanced in the quest for insecticides collected from toxic plants supposed to be less aggressive to the milieu (BUENO; BUENO, 2011) but harmful to leaf-cutting ants (GANDRA et al, 2011;SOUZA et al, 2012;GOMES et al, 2016). The application of their extracts is made directly on the fungus developed in culture media or on the ants themselves (BUENO et al, 2004;FRANCO et al, 2013;SANTOS et al, 2013;MORAIS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(ALMEIDA et al, 2007), Raulinoa echinata Cowan (BIAVATTI et al, 2005), and Citrus limon (L.) Burm (FERNANDES et al, 2002). Esenbeckia grandiflora Mart is active against Atta sexdens sexdens Lineu, 1758 (GOMES et al, 2016).…”
Section: Introductionmentioning
confidence: 99%